The function of internal audit as a structural model of corporate governance in the modern economy - Bolatkyzy, S.; Umirzakova, M.A.; Shilmanova, А.М.; Butabayeva, N.K.; Shakirova, G.A. (BUKETOV BUSINESS REVIEW, 2023)
Object: The purpose of this study is to determine the function of internal audit, as well as to identify the effectiveness in the structural model of corporate governance in large enterprises, as well as to determine the impact of risk-based internal audit on corporate governance. Methods: Research methods are research design, data collection tools, data collection procedures and analysis details, Smart PLS, which helped to achieve the goals of research work.SmartPLS is a multifactorial structural model that, through questionnaires, helps to achieve the most accurate results in scientific research. Findings: The results showed that in practice the tasks facing the internal audit were not confirmed, since the moderator of the influence of the internal audit strategy is influenced by other factors on corporate governance.Based on the results of the criteria for assessing the significance of the structural model in the above analysis, it turned out that the tasks facing internal audit do not affect the dependent variable of the internal audit strategy. The results showed that in practice, the factors influencing internal audit do not show a strong dependence, since the moderator of the influence of the internal audit strategy affects other factors on corporate governance. That is, according to the results of the criteria for assessing the significance of the structural model in the article, it is noticeable that the tasks facing internal audit do not affect the dependent variable of the internal audit strategy. Conclusions:Based on the results, it was revealed that the internal audit strategy directly affects the corporate governance of the enterprise. The internal audit tasks showed a low correlation dependence, the correlation regarding the internal audit task was not confirmed. For this reason, for the effectiveness of corporate governance, it is necessary to have a reasonable internal audit is an integral requirement of corporate governance.